Hemodynamics in young athletes following high-intensity interval or moderate-intensity continuous training - Ketelhut, S.; Kirchenberge, T.; Ketelhut, R. G. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: The present study aimed to investigate the effects of high-intensity interval training (HIIT) versus moderate-intensity continuous training (MICT) on blood pressure (BP) and parameters of arterial stiffness in young athletes. METHODS: Seventeen rowers (aged 15±1.3 years) were randomized into an intervention group (IG, N.=10) and the control group (CG, N.=7). During an 8-week intervention period, the IG completed a HIIT on the rowing ergometer twice-weekly (2×4×2 min at ˜95% of maximum heart rate [HRmax], 60 s rest) in addition to the regular rowing training (3×/week MICT 70-90 min, ˜70% HRmax). The CG completed the regular normal rowing training and, instead of the HIIT units, two additional MICT units (70-90 min, ˜70% HRmax). Before and after the intervention period, hemodynamic parameters were recorded non-invasively in both groups. RESULTS: After the intervention period, there was a significant decrease in peripheral systolic (P=0.01) and diastolic (P=0.05) BP, as well as in central systolic (P=0.05) and diastolic BP (P=0.03) in the IG. Furthermore, pulse wave velocity (PWV) (P=0.05) was significantly reduced. Analysis of intervention effects revealed significant between-group differences in central diastolic BP (P=0.05), in augmentation pressure (P=0.02), and in augmentation index (P=0.006) favoring IG. The CG showed no significant changes in the respected parameters throughout the intervention. CONCLUSIONS: Already in adolescent athletes, a HIIT intervention has beneficial effects on peripheral and central BP as well as on PWV, augmentation pressure, and augmentation index.